Beiträge zur Insekten-Fauna der DDR: Coleoptera - Helodidae. 17. Beitrag zur Kenntnis der Helodidae. - Klausnitzer, Bernhard (Contributions to Entomology = Beiträge zur Entomologie, 1971)
The author's own collection and all other collections accessible to him enabled him to revise 4.749 Helodidae. This material and a critical study of existing publications made it possible to give a survey of the Helodidae of the GDR. A total of 20 species were identified on this territory. Of special interest are Cyphon punctipennis Sharp, which had not been known before from the GDR, and Helodes elongata Tournier, no certain finds of which had been known from Central Europe. The new species Helodes kölleri Klausnitzer belonging to the Helodes minuta group was identified in three places. Finds of Helodes pseudominuta Klausnitzer may be expected, finds of Helodes flavicollis Kiesenwetter and Helodes hausmanni (Gredler) are not impossible. To facilitate the determination of this difficult family, a key is given, which did not exist in a revised form before except for the genus Cyphon Paykull.